2012
DOI: 10.1039/c2ob06714e
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-supported syntheses of thiophene-containing compounds using a new type of traceless linker

Abstract: A new type of traceless linker is described for use in polymer-supported (PS) syntheses of thiophene-containing compounds. It is based on the cleavage of PS aryl 2-thienyl ketones by a mixture of potassium t-butoxide and water (typical mol ratio 10:3) in an ethereal solvent. Cleavage occurs to give the soluble thiophene-containing product. The method is used to prepare a range of eight thiophene-containing compounds including a terthiophene and a dialkylquaterthiophene. PS unsymmetrical diaryl ketones incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Ben-Haida et al developed a unique approach, consisting of the cleavage of polymer-supported aryl 2-thienyl ketones using a mixture of potassium tert-butoxide and water. The cleavage reaction affords the terthiophene as product [ 52 ]. Leriche et al reported in their study the formation of terthiophenes as side product: their work pursued the synthesis of star-shaped phosphorous oligothiophene derivatives, however, during the coupling reaction, with a stoichiometric amount of 2-tributylstannylthiophene and in the presence of Pd(PPh3)4 as catalyst undesired terthiophene was obtained in 20% yield [ 53 ].…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
“…Ben-Haida et al developed a unique approach, consisting of the cleavage of polymer-supported aryl 2-thienyl ketones using a mixture of potassium tert-butoxide and water. The cleavage reaction affords the terthiophene as product [ 52 ]. Leriche et al reported in their study the formation of terthiophenes as side product: their work pursued the synthesis of star-shaped phosphorous oligothiophene derivatives, however, during the coupling reaction, with a stoichiometric amount of 2-tributylstannylthiophene and in the presence of Pd(PPh3)4 as catalyst undesired terthiophene was obtained in 20% yield [ 53 ].…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
“…Ben-Haida and Hodge reported the synthesis of eight thiophene-containing compounds with conjugated π-electron systems using a new traceless ketone linker. 47 The linker was prepared from chloromethyl Merrifield resin 1 and 4-hydroxyphenyl 2-thienyl ketone 58 (Scheme 9). To diversify the thiophene ring, the bromo derivative 59 was subjected to Suzuki coupling with arylboronic acids 63a−63d.…”
Section: Ketone Linkersmentioning
confidence: 99%
“…The recent interest in oligomers with conjugated π-electron systems due to their potential applications in molecular electronics has driven the development of efficient synthetic routes for their preparation. Ben-Haida and Hodge reported the synthesis of eight thiophene-containing compounds with conjugated π-electron systems using a new traceless ketone linker . The linker was prepared from chloromethyl Merrifield resin 1 and 4-hydroxyphenyl 2-thienyl ketone 58 (Scheme ).…”
Section: C–h Linkersmentioning
confidence: 99%
“…It provided a procedure whereby reagents and byproducts were simply removed by filtration, and recrystallization of any intermediates was eliminated. Other types of π-conjugated oligomers have been reported and synthesized by a solid-phase approach, including oligo-(dialkylfluorene)­s, oligo-(triarylamine)­s, and alternating cooligomers thereof . Also notable is that Burke et al developed a new type of catch-and-release purification protocol for N -methyliminodiacetic acid (MIDA)-boronate-containing intermediates. , MIDA boronates absorbed on silica gel were purified by switching the eluent, thanks to their binary elution properties.…”
Section: Introductionmentioning
confidence: 99%